Students with Migration Background in the University of Crete: A Biographical and Factional Analysis - Kontogianni, Dionysia; Michelakaki, Theodosia; Papalexopoulou, Efthimia (Études helléniques / Hellenic Studies, 2013)
This article focuses on the students of immigrant origin who have followed mainstream primary and secondary education and have entered the University of Crete through the national examination. Fifteen migratory biographies are analyzed qualitatively and indicate that the students, through a rough course of schooling, learning Greek and being integrated into the Greek society, have succeeded to enroll to the University, but they still lack the opportunity of being granted citizenship and feel full members of the society. The contradiction between accepting foreign schoolchildren into the education system and depriving them from full legal rights is an uprising issue to be dealt with by the state.